Understanding the mechanisms of viral induced asthma: New therapeutic directions - Hansbro, Nicole G. (Pharmacol Ther, 2008)
Asthma is a common and debilitating disease that has substantially increased in prevalence in Western Societies in the last 2 decades. Respiratory tract infections by respiratory syncytial virus (RSV) and rhinovirus (RV) are widely implicated as common causes of the induction and exacerbation of asthma. These infections in early life are associated with the induction of wheeze that may progress to the development of asthma. Infections may also promote airway inflammation and enhance T helper type 2 lymphocyte (Th2 cell) responses that result in exacerbations of established asthma. The mechanisms of how RSV and RV induce and exacerbate asthma are currently being elucidated by clinical studies, in vitro work with human cells and animal models of disease. This research has led to many potential therapeutic strategies and, although none are yet part of clinical practise, they show much promise for the prevention and treatment of viral disease and subsequent asthma.